A Current Perspective on the Assessment of Prevalence of Dengue Cases in a Territory Care Hospital Bangalore and Impact of Clinical Pharmacist Mediated Patient Counseling – A Prospective Study - Muchukota, Sushma; L, Bhoomika; C, Dinesh M; Yadav, Vinutha N; C, Kavana.; Mathappan, Rinku (Asian Journal of Pharmaceutical Research and Development, 2019)
Background: Dengue is an Infectious viral disease caused by the dengue virus. Dengue fever is caused by one of four types of dengue virus. It is transmitted by “Aedes aegypti mosquito”. Symptoms include Fever, Arthralgia, Myalgia and Headache etc.,. Dengue is mosquito-borne viral illness. Fluid and electrolyte losses, dengue shock syndrome, residual brain damage, Febrile convulsions, Low platelet count, Significant bleeding, Liver damage are some of the complications of dengue fever Aim The present hospital study aims to illustrate the frequency, distribution and case fatality of dengue fever based on the variables such as age, sex and impact of clinical pharmacist mediated patient counseling. Objectives: To evaluate the perspectives on assessment of prevalence of the dengue fever and the impact of clinical pharmacist mediated in patient counseling. To estimate the prevalence of dengue fever, educate and create awareness about dengue fever and prevent further complications. Methodology: A prospective Observational study was carried out among 150 patients for a period of 4 months from June 2019 to September 2019 in ESI hospital Indiranagar, Bangalore. Results: Dengue fever is mostly seen among the age groups between 15-55 yrs. An excess of males were found among reported dengue cases than females 54.6 % were males and 45.3% were females. High proportion of cases were reported in adult age groups (25-35 years) in both males and females, Out of 150 cases Dengue fever 89.3% , Dengue hemorrhagic fever is 7.3% and Dengue shock syndrome 3.33% is fatality rate and the outcome of dengue fever is 94.66% survival rate and 5.3% death rate. Conclusion: The patients with Dengue fever 89.3% and other types are DHF, DSS 7.3% and 3.3% out of them patients with thrombocytopenia is 64.66% and the platelet transfusion done in 65 patients (43.33%) out of them 142 patients (94.6%) are survived and the death rate is 5.3% the early identification of complications might have increased the survival rate and decreases the mortality in Dengue fever patients.